A review of the international early recommendations for departments organization and cancer management priorities during the global COVID-19 pandemic: applicability in low- and middle-income countries. (August 2020) - Belkacemi, Yazid; Grellier, Noemie; Ghith, Sahar; Debbi, Kamel; Coraggio, Gabriele; Bounedjar, Adda; Samlali, Redouane; Tsoutsou, Pauletta G.; Ozsahin, Mahmut; Chauvet, Marie-Pierre; Turkan, Sedat; Boussen, Hamouda; et al.
Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by a new virus that has never been identified in humans before. COVID-19 caused at the time of writing of this article, 2.5 million cases of infections in 193 countries with 165, 000 deaths, including two-third in Europe. In this context, Oncology Departments of the affected countries had to adapt quickly their health system care and establish new organizations and priorities. Thus, numerous recommendations and therapeutic options have been reported to optimize therapy delivery to patients with chronic disease and cancer. Obviously, while these cancer care recommendations are immediately applicable in Europe, they may not be applicable in certain emerging and low- and middle-income countries (LMICs). In this review, we aimed to summarize these international guidelines in accordance with cancer types, making a synthesis for daily practice to protect patients, staff and tailor anti-cancer therapy delivery taking into account patients/tumour criteria and tools availability. Thus, we will discuss their applicability in the LMICs with different organizations, limited means and different constraints. Highlights: The first recommendations concerned mainly staff and patients with cancer protection. More than half of the worldwide cancers are diagnosed in low- and middle-income countries (LMICs). Organization in accordance with available means: main key for anti-cancer strategy in LMICs. European recommendations applicability for coronavirus disease 2019 (COVID-19) pandemic is questioned in LMICs. Amplification of pandemic effects on both COVID and cancer is to be feared in LMICs.